Integrating gut microbiome and neuroplasticity genomics in alcohol use disorder therapy - Ilias Koutromanos; Evangelia Legaki; Nikolas Dovrolis; Efthimios Vassilopoulos; Arthur Stem; Vasilis Vasiliou; Elias Tzavellas; Maria Gazouli (Human Genomics)
Abstract Background Alcohol Use Disorder (AUD) is a chronic neuropsychiatric condition with substantial public health impact. The interplay between gut microbiota and neuroplasticity-related genes presents a novel approach to understand AUD pathophysiology and treatment response. While microbial dysbiosis has been implicated in AUD, its correlation with gene expression changes in neuroplasticity pathways remains unexplored. This study investigates microbiome composition, microbial metabolic pathways, and their correlation with neuroplasticity-related genes in AUD patients undergoing treatment. Methods We conducted a prospective observational study integrating gut microbiome 16S rRNA sequencing and host neuroplasticity-related gene expression profiling in AUD patients undergoing treatment which combines psychotherapeutic intervention along with oral diazepam administration followed by Pythagorean Self Awareness Intervention. Patients were classified as responders or non-responders, and microbial composition, functional pathways, and host-microbiota interactions were analyzed using multi-omic correlation frameworks. Results Responders exhibited a microbiome enriched in short-chain fatty acid (SCFA)-producing bacteria (e.g., Lachnospiraceae), linked to gut barrier integrity and neurotransmitter synthesis. In contrast, non-responders demonstrated enrichment of inflammation-associated taxa (Succinivibrionaceae) and oxidative stress-related metabolic pathways. Correlation analysis revealed microbiome-mediated modulation of neuroplasticity-related genes measured from peripheral blood, including BDNF, GRIA1, CAMK2G, and EGR family genes, suggesting a gut-brain-genomic axis in AUD treatment response. Conclusions This study highlights the role of gut microbiota as a modulator of neuroplasticity-related gene expression in AUD patients. Integrating microbiome and host genomic signatures could improve biomarker-based prediction of treatment response and inform precision medicine approaches for AUD. Future studies should expand these findings by incorporating multi-omic approaches, including epigenomics and exposomics, to refine microbiome-targeted interventions for addiction therapy.